A dual functional collagen scaffold coordinates angiogenesis and inflammation for diabetic wound healing. (7th October 2020) - Long, Ge; Liu, Dingyang; He, Xi; Shen, Yeyu; Zhao, Yannan; Hou, Xianglin; Chen, Bing; OuYang, Wen; Dai, Jianwu; Li, Xing
Abstract : Chronic diabetic wounds, which are associated with persistent inflammation and impaired angiogenesis, occur frequently in diabetic patients. Abstract : Chronic diabetic wounds, which are associated with persistent inflammation and impaired angiogenesis, occur frequently in diabetic patients. Some studies have shown that separate administration of vascular endothelial growth factor (VEGF) or stromal cell derived factor 1α (SDF-1α) exhibited a therapeutic effect in promoting angiogenesis in the wound healing process. In this study, a collagen membrane is prepared as a drug delivery scaffold to investigate whether combined administration of SDF-1α and VEGF has a synergistic therapeutic effect on diabetic wound healing. We specifically fused a collagen-binding domain (CBD) with SDF-1α and VEGF separately, and sustained release of the two recombinant proteins from the collagen scaffold is successfully observed. Meanwhile, when a CBD-VEGF and CBD-SDF-1α co-modified scaffold is implanted in a diabetic rat skin wound model, it not only shows a synergistic effect in facilitating angiogenesis but also reduces inflammation in the short-term. Moreover, long-term results reveal that the co-modified scaffold is also able to enhance rapid wound healing, promote blood vessel regeneration, and assist cell proliferation, re-epithelialization and extracellular matrix accumulation. Taken together, our study indicates that the CBD-VEGF and CBD-SDF-1α co-modified scaffold helps in quick recovery from diabetic wounds by coordinating angiogenesis and inflammation.